Effectiveness and Tolerability of Dronabinol Use in Patients with Chronic Pain: A Retrospective Analysis of 12-Week Open-Label Real-World Data Provided by the German Pain e-Registry. Issue 8 (1st February 2022) - Ueberall, Michael A; Horlemann, Johannes; Schuermann, Norbert; Kalaba, Maja; Ware, Mark A
Abstract: Objective: To evaluate the effectiveness of Δ9-tetrahydrocannabinol (dronabinol [DRO]) as an add-on treatment in patients with refractory chronic pain (CP). Methods: An exploratory retrospective analysis of 12-week data provided by the German Pain e-Registry on adult patients with treatment refractory CP who received DRO. Results: Between March 10, 2017, and June 30, 2019, the German Pain e-Registry collected information on 89, 095 patients with pain, of whom 1, 145 patients (1.3%) received DRO (53.8% female, mean ± standard deviation age: 56.9 ± 10.6 years), and 70.0% documented use for the entire 12-week evaluation period. The average DRO daily dose was 15.8 ± 7.5 mg, typically in three divided doses (average DRO dose of 5.3 ± 2.1 mg). Average 24-hour pain intensity decreased from 46.3 ± 16.1 to 26.8 ± 18.7 mm on a visual analog scale (absolute visual analog scale difference: –19.5 ± 17.3; P  < 0.001). Among patients who completed follow-up, an improvement from baseline of at least 50% was documented for pain (46.5%), activities of daily living (39%), quality of life (31.4%), and sleep (35.3%). A total of 536 patients (46.8%) reported at least one of 1, 617 drug-related adverse events, none of which were serious, and 248 patients (21.7%) stopped treatment. Over the 12-week period, 59.0% of patients reported a reduction of other pain treatments, and 7.8% reported a complete cessation of any other pharmacological pain treatments. Conclusion: Add-on treatment with DRO in patients with refractory CP was well tolerated and associated with a significant improvement.